Participação social no planejamento e gestão urbana: o orçamento participativo de Olinda - Duchrow, Alina D'Alva (2004)
This work aims to identify and analyze the determinant factors for the establishment and consolidation of the social participation within the Urban Planning and Management,having as an empirical reference the process of public debate regarding the participative budget developed in the municipality of Olinda in the state of Pernambuco- Brazil. Through the theoretical discussions concerning the participative urban planning and management as well as the empirical studies about the experiences of participative budget in Brazil, are identified the variables which may influence the social participation in the urban management system. These variables are then tested against the study case occurring in the municipality of Olinda, in order to verify the quality and development of the proposed participatory process.